Student management system (SMS) - Pui, Hock Young (2014)
Student Management System (SMS) is software application for the education that can be used to managed student information and data. This system is designed for primary school to help administrators and teachers in the management of students. Students Management System consists of four modules including Teachers, Students and Parents Profile, Student Exam Results, Comment Reply and SMS notification. Teachers can use this system to register information of student and managing parents and student profile. Teachers can view results of the students in graph format to know their performance. Besides that, teachers also can send the student results to parents through Short Message Service (SMS). For the parents, they can login to system and view their children examination results and also graph for know their performance. This system also provides a communication platform for parents and teachers. Thus, by using this system can benefits to administrators, teachers and parents.